2017
DOI: 10.1038/srep45126
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of caspase-1 and caspase-11 in infection and inflammation

Abstract: Caspase-1, also known as interleukin-1β (IL-1β)-converting enzyme (ICE), regulates antimicrobial host defense, tissue repair, tumorigenesis, metabolism and membrane biogenesis. On activation within an inflammasome complex, caspase-1 induces pyroptosis and converts pro-IL-1β and pro-IL-18 into their biologically active forms. “ICE−/−” or “Casp1−/−” mice generated using 129 embryonic stem cells carry a 129-associated inactivating passenger mutation on the caspase-11 locus, essentially making them deficient in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 106 publications
4
93
1
1
Order By: Relevance
“…Nlrp3 −/− , Pycard −/− , Casp11 −/− , Casp1 −/− Casp11 −/− (He et al, 2016), Nlrp6 −/− (Chen et al, 2011), Il18 −/− (Seregin et al, 2017), Aim2 −/− , Il1b −/− (Seo et al, 2015), Casp1 −/− (Man et al, 2017), and Gsdmd −/− mice (Rauch et al, 2017) on C57BL/6 background have been reported. C57BL/6 WT and Ifnar1 −/− (Muller et al, 1994) mice were purchased from Jackson Laboratories.…”
Section: Star Methodsmentioning
confidence: 99%
“…Nlrp3 −/− , Pycard −/− , Casp11 −/− , Casp1 −/− Casp11 −/− (He et al, 2016), Nlrp6 −/− (Chen et al, 2011), Il18 −/− (Seregin et al, 2017), Aim2 −/− , Il1b −/− (Seo et al, 2015), Casp1 −/− (Man et al, 2017), and Gsdmd −/− mice (Rauch et al, 2017) on C57BL/6 background have been reported. C57BL/6 WT and Ifnar1 −/− (Muller et al, 1994) mice were purchased from Jackson Laboratories.…”
Section: Star Methodsmentioning
confidence: 99%
“…160 LPS and oxAPC elicit caspase-11-induced inflammasome speck formation and IL-1 release, but not pyroptosis, in DCs. 160 In addition, caspase-11 contributes to host resistance to the fungal pathogen Aspergillus fumigatus in vivo, 161 revealing a biologic role for caspase-11 in host defense against pathogens other than Gram-negative bacteria. Overall, substantial advances have been made in our understanding of the noncanonical NLRP3 inflammasome.…”
Section: Noncanonical Nlrp3 Inflammasomementioning
confidence: 99%
“…In mice, this activation is necessary for early control of L. monocytogenes via production of IL-18 and interferon (IFN)γ. However, caspase-1 appears dispensable for acquisition of sterilizing adaptive immunity and no role for caspase-11 was identified in C57BL/6 mice [4749]. Using cell culture models, several studies showed that L. monocytogenes activates NLRP3 and AIM2 inflammasomes.…”
Section: Pathogens Differentially Interfere With the Inflammasomes Anmentioning
confidence: 99%
“…Thus, physiological (nutrient starvation), pharmacological (rapamycin, sodium valproate, vitamin D), or immunological agonists of autophagy (TNF, IFN-α) stimulate mycobacterial phagosome maturation, allowing the host cell to control M.tb infection [163]. Specifically, IFN-γ acts on promoting autophagy via the induction of TNF and the immunity-related GTPase protein IRGM1 [4951,167,168]. The role of IRGM1 in induction of autophagy has been well characterized in several human polymorphism studies, as well as the potential role of other closely related to autophagy genes such as P 2 X 7 , VDR, NOD2 , and TLR8 (summarized in Ref.…”
Section: Pathogens Differentially Interfere With the Inflammasomes Anmentioning
confidence: 99%